CD28/B7 Deficiency Attenuates Systolic Overload-Induced Congestive Heart Failure, Myocardial and Pulmonary Inflammation, and Activated T Cell Accumulation in the Heart and Lungs. Issue 3 (September 2016) - Wang, Huan; Kwak, Dongmin; Fassett, John; Hou, Lei; Xu, Xin; Burbach, Brandon J.; Thenappan, Thenappan; Xu, Yawei; Ge, Jun-bo; Shimizu, Yoji; Bache, Robert J.; Chen, Yingjie
Abstract : The inflammatory response regulates congestive heart failure (CHF) development. T cell activation plays an important role in tissue inflammation. We postulate that CD28 or B7 deficiency inhibits T cell activation and attenuates CHF development by reducing systemic, cardiac, and pulmonary inflammation. We demonstrated that chronic pressure overload–induced end-stage CHF in mice is characterized by profound accumulation of activated effector T cells (CD3 + CD44 high cells) in the lungs and a mild but significant increase of these cells in the heart. In knockout mice lacking either CD28 or B7, there was a dramatic reduction in the accumulation of activated effector T cells in both hearts and lungs of mice under control conditions and after transverse aortic constriction. CD28 or B7 knockout significantly attenuated transverse aortic constriction–induced CHF development, as indicated by less increase of heart and lung weight and less reduction of left ventricle contractility. CD28 or B7 knockout also significantly reduced transverse aortic constriction–induced CD45 + leukocyte, T cell, and macrophage infiltration in hearts and lungs, lowered proinflammatory cytokine expression (such as tumor necrosis factor-α and interleukin-1β) in lungs. Furthermore, CD28/B7 blockade by CTLA4-Ig treatment (250 μg/mouse every 3 days) attenuated transverse aortic constriction–induced T cell activation, left ventricle hypertrophy, and left ventricle dysfunction. Our data indicate that CD28/B7 deficiency inhibits activated effector T cell accumulation, reduces myocardial and pulmonary inflammation, and attenuates the development of CHF. Our findings suggest that strategies targeting T cell activation may be useful in treating CHF. Abstract : Supplemental Digital Content is available in the text.